2015
DOI: 10.1007/s10534-015-9899-8
|View full text |Cite
|
Sign up to set email alerts
|

Metal concentrations in hair of patients with various head and neck cancers as a diagnostic aid

Abstract: Head and neck cancers are one of the most frequent cancers worldwide. This paper attempts to evaluate disturbances of homeostasis of the necessary elements (calcium, magnesium, zinc, copper, iron, manganese) and changes in the levels of toxic metals (lead, cadmium, cobalt, chromium VI) in hair of patients with head and neck cancers, as well as people without a diagnosed neoplastic disease. In order to quantify the necessary elements and toxic metals, a method using ICP-MS and ICP-OES techniques had been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
0
22
0
4
Order By: Relevance
“…It has been reported that mean blood levels of chromium and nickel (55.15 and 111.60 μg/l) among patients with HNSCC were significantly higher than those of controls (37.04 and 30.50 μg/l, respectively). Higher concentrations of these metals were, among others, caused by tobacco smoking or exposure to second‐hand tobacco smoke (SHS) that in consequence increased the risk of cancer …”
Section: Toxicity Of Tobacco Smokementioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that mean blood levels of chromium and nickel (55.15 and 111.60 μg/l) among patients with HNSCC were significantly higher than those of controls (37.04 and 30.50 μg/l, respectively). Higher concentrations of these metals were, among others, caused by tobacco smoking or exposure to second‐hand tobacco smoke (SHS) that in consequence increased the risk of cancer …”
Section: Toxicity Of Tobacco Smokementioning
confidence: 99%
“…7,35 DNA lesions can also be caused by exposure to metals present in tobacco smoke. 36,37 Among more than 30 metals found in tobacco smoke seven were classified by IARC as carcinogenic. Five of them are proven human carcinogens.…”
Section: Toxicity Of Tobacco Smokementioning
confidence: 99%
See 1 more Smart Citation
“…Występujące zaburzenia w gospodarce tymi pierwiastkami mogą skutkować nieprawidłowym funkcjonowaniem komórek i prowadzić do stanu chorobowego. Jony cynku i magnezu wchodzą w skład enzymów antyoksydacyjnych, stanowiących naturalną barierę w rozwoju nowotworów [5,7,8,9,10]. Niskie stężenie tychże pierwiastków może również wiązać się ze zwiększoną insulinoopornością i przewlekłymi stanami zapalnymi [5,4,11].…”
Section: Słowa Kluczoweunclassified
“…Analiza zawartości Zn i Mg we krwi nie oddaje w pełni ich rzeczywistego stężenia w organizmie ze względu na okresowe wahania [9,10,14]. Pomiar przeprowadzony na paznokciach lub włosach dobrze odwzorowuje przeciętną zawartość tych pierwiastków w organizmie ze względu na długi czas związany z ich przyrostem.…”
Section: Słowa Kluczoweunclassified